Students’ Perceptions of Innovative Learning Media as a Support System for Inclusive Education - Yuni Sari Amalia (Universitas Airlangga, 2022)
All students, without exception, are expected to have an equal opportunity of acquiring higher education. Many universities in Indonesia including Universitas Airlangga accept students with disabilities. However, the availability and use of learning materials for these students are scarce. The study aimed to understand the students' perceptions on this issue, particularly for students with visual and hearing impairments. The study includes 80 participants consisting of regular students and students with special needs in Universitas Airlangga. The study used a questionnaire to collect students’ perspective on learning media provided by Universitas Airlangga. The findings of the study revealed how the majority of students at Universitas Airlangga considered learning materials and media available cannot be used to its full potential by students with special needs. Moreover, the policies have not been adjusted to the needs of students with special needs. Moreover, students expected support system to help the learning process of students with special needs. Lastly, the participants’ responds on the questionnaire show positive opinions on the initiative and calls for the need to scale up and improve the support system.